THE IMPLEMENTATION OF ACCELERATED LEARNING MODEL (AL) USING VISUAL, AUDITORY, KINESTHETIC APPROACH (VAK), TO INCREASE LEARNING OUTCOMES ON INFORMATION COMMUNICATION TECHNOLOGY (ICT) FOR THE X6 GRADE STUDENTS’ OF SMAN 2 SINGARAJA IN THE ACADEMIC YEAR 2012/2013 - Dewa Putu Gede Eka Kurniadi (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
This study aims to improve students’ learning outcomes on the subject of Information and Communication Technology (ICT) by applying Accelerated Learning (AL) model. AL utilizes visual, auditory, and kinesthetic (VAK) approach as well as   students' response to evaluate its application.The study was conducted at SMAN 2 Singaraja with participants from X6 grade  students (36 students), school year 2012/2013. The design of this research is Classroom Action Research (CAR), which consists of 2 cycles. The data collected in this study is the result of students’ learning and response to the application of AL on ICT subjects. The student learning outcomes data collected through cognitive test and affective and psychomotor observation sheet, while the students' response data was collected via enclosed sheet questionnaires.The result shows that (1) there is an increase in students’ learning outcomes. This is evident from the classical completion that the students obtained: 52,78% and 80,00% in the first and second cycle respectively. The learning outcomes have increased by 27,22%. (2) The average students’ response to the application of the AL model is positive: 45.62% of the questionnaires. The researcher concludes that the application of the AL model which uses the VAK approach can improve the learning outcomes on the subjects of ICT. Furthermore, it has also received a positive response from the students.